PENGARUH TERAPI RELAKSASI BENSON TERHADAP KECEMASAN PASIEN PRE OPERASI DI RSUD KAB TANGERANG - irma, Irma Yanti Kurnia Sari; Nining Sriningsih; Ayu Pratiwi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Surgery is a medical procedure that involves surgical intervention in the body to improve physical function. Surgery can cause excessive fear and anxiety and can lead to complications. Based on a preliminary study by researches when PKK showed data there ±50 people experiencing anxiety. To reduce anxiety, pharmacological and non-pharmacological techniques is Benson Relaxation Therapy which is carried out by deep breathing and accompanied by beliefs held by the patient to achieve a relaxed state. The purpose of study :To determine the effect of Benson’s Relaxation Therapy on anxiety levels in preoperative patients in the patient installation of Tangerang District Hospital. Research Method : This research uses pre-eksperimental with One Group Pre-Test Post-Test with Incindental Sampling 22 respondents, using questionnaire sheets, Standard Operating Procedures and Wilcoxon test analysis. The Results of the study :Using the analysis of the Shapiro-Wilk normalization test and the Wilcoxon test with the results of p value =0.000 which means <0,005. Conclusion :There is an effect of Benson Relaxation Therapy on the anxiety levels of preoperative patients.